A qualitative case study of traditional healing approaches to mental health and emotional well-being in African communities. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2026)
Background Mental health disorders are increasing globally, yet many African communities continue to rely on traditional healing practices for emotional and psychological well-being. Traditional healers often function as spiritual guides and informal therapists, addressing conditions such as depression, anxiety, grief and trauma. This study explored the contribution of traditional healing to mental health support in rural African communities and examined perceptions of effectiveness, trust, and collaboration with formal healthcare services. Methods A qualitative case study design was employed. Data were collected through in-depth interviews and focus group discussions with 30 participants from two rural communities in KwaZulu-Natal, South Africa. Participants were purposively selected and included 10 traditional healers, 10 community members with lived experience of traditional mental health care, and 10 community health workers. Data were analysed using thematic content analysis. Results Of the 30 participants, 60% were female, and 40% were male, with ages ranging from 28 to 67 years (mean age: 45 years). Among traditional healers, 80% had more than ten years of practice experience, while half of the community members reported repeated use of traditional mental health services. Community health workers had an average of five years of service. Findings revealed that traditional healing practices are deeply embedded in spiritual beliefs, ancestral communication, and communal support systems. Rituals, herbal remedies, and cleansing ceremonies were regarded as central to emotional healing, particularly for spiritually or family-related distress. Traditional healers were highly trusted, whereas collaboration between traditional and biomedical practitioners was limited, largely due to mutual scepticism and the absence of formal integration frameworks. Conclusion Traditional healing plays a vital and culturally relevant role in mental health support in rural African communities, especially where formal services are limited. Recommendation Policy frameworks that promote respectful collaboration, culturally sensitive training, and community education are essential to support integrated mental health care models.